A Deep‐Cycle Aqueous Zinc‐Ion Battery Containing an Oxygen‐Deficient Vanadium Oxide Cathode. (27th December 2019) - Liao, Meng; Wang, Jiawei; Ye, Lei; Sun, Hao; Wen, Yunzhou; Wang, Chuang; Sun, Xuemei; Wang, Bingjie; Peng, Huisheng
Abstract: Rechargeable aqueous zinc‐ion batteries are attractive because of their inherent safety, low cost, and high energy density. However, viable cathode materials (such as vanadium oxides) suffer from strong Coulombic ion–lattice interactions with divalent Zn 2+, thereby limiting stability when cycled at a high charge/discharge depth with high capacity. A synthetic strategy is reported for an oxygen‐deficient vanadium oxide cathode in which facilitated Zn 2+ reaction kinetic enhance capacity and Zn 2+ pathways for high reversibility. The benefits for the robust cathode are evident in its performance metrics; the aqueous Zn battery shows an unprecedented stability over 200 cycles with a high specific capacity of approximately 400 mAh g −1, achieving 95 % utilization of its theoretical capacity, and a long cycle life up to 2 000 cycles at a high cathode utilization efficiency of 67 %. This work opens up a new avenue for synthesis of novel cathode materials with an oxygen‐deficient structure for use in advanced batteries. Abstract : Eine leistungsstarke Kathode zum Einsatz in tiefentladbaren wässrigen Zn‐Ionen‐Batterien wurde durch Extraktion von Sauerstoff aus Vanadiumoxidgittern hergestellt. Die Mobilität von Zn 2+ wird erleichtert, wodurch die Kapazität und Reversibilität der Batterie verbessert werden. Die Kathode erzielt eine Stabilität von 200 Zyklen mit einer hohen Kapazität von 400 mAh g −1 und einer Nutzungseffizienz von 95 % sowie eine Langzeitstabilität von 2000 Zyklen bei einer Nutzungseffizienz von 67 %.